Pemanfaatan Barang Gadai Oleh Rȃhin dan Murtahin Tinjauan Fiqh Madzhab Syafi’i dan Hambali - ahmad irsadul ibad (Journal of Islamic Business Law, 2018)
This study aims to discuss about the guarantee goods (marhun) as debt guarantees, in terms of utilization of the scholars madhhab disputes good utilization done by râhin by murtahin. The type of research used is library research (library research) by using the method of approach concept and comparative approach (comparative approach). Primary data used in this research is, Fiqh al-Islami wa Adillatuhu work Wahbah az-Zuhaily, Fiqh ala Madzahibil Arba'ah by Abdurrahman al-Jaziri, Fiqh As-Sunnah by Sayyid Sabiq, and others. As well as secondary data that use books related to the research material. After the research, it is found the result of the research about the utilization of pawn goods by râhin and murtahin in fiqh madzhab Syafi'i and Hambali, that is, After the research is found result of research, that is first use marhun by râhin both madhhab this same opinion that, Syafi'i, and Hambali said that using the lien is prohibited, unless there is permission from murtahin. Second, the use of marhun by murtahin rMadzhab Syafi ', ​​Murtahin may take advantage of marhun if diizini by râhin, While Hambali School if marhun in the form of inanimate objects then murtahin prohibited to use, but if marhun in the form of animals that can be ridden and milked then it is used by murtahin.